Strategi Pengembangan Homestay Sebagai Sarana Promosi Desa Wisata Sawarna - Wartha, Joni; Cessa Agustin, Syafira; Fadlurahman, Hafizd (VINICHO MEDIA PUBLISINDO, 2023)
This community service provides training homestay development strategies as a means of promotion in the context of increasing tourism in the Sawarna Tourism Town, Banten. Focusing on a participatory approach, the research details strategic steps to establish homestays that not only utilize the potential of local resources, but also integrate Sitamanbumi and Batour applications as modern promotional tools. Involving training for homestay managers and utilization of digital technology, the research aims to create an authentic tourist experience while supporting local economic growth. By exploring the potential of tourism and community empowerment, this research contributes to a practical understanding of how homestays can be an important pillar in the promotion of tourist destinations and build positive impact within local communities.